2022
DOI: 10.3390/systems10050179
|View full text |Cite
|
Sign up to set email alerts
|

Household Registration, Old-Age Insurance, and Consumption: Evidence from China

Abstract: Understanding migrants’ status and socio-economic outcomes can help develop immigrant societies. Household registration in China plays a vital role in migrants’ status to provide an excellent research environment. Based on panel data from the Institute of Social Science Survey (CFPS) from 2012 to 2020, this paper investigates the impact of various old-age insurance schemes on urban residents’ consumption with the difference in household registration. The result shows that insurance increases consumption more i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…In terms of population burden ratio, there is a positive association between Child share and consumption. Consistent with prior literature, positive effects are also existed in higher income households (41,44).…”
Section: Baseline Regression Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In terms of population burden ratio, there is a positive association between Child share and consumption. Consistent with prior literature, positive effects are also existed in higher income households (41,44).…”
Section: Baseline Regression Resultssupporting
confidence: 88%
“…Based on the existing literature and field experience, we further included three levels of control variables ( 5 , 13 , 41 ). First, in terms of respondent characteristics, basic information and social attitude were included, such as , , , marital status ( , , ), , and working status ( , , ).…”
Section: Methodsmentioning
confidence: 99%
“…Research shows that in high-income plans, the increase in insurance-induced consumption is caused by a lower incentive to save defensively. [5] Despite this, there are relatively few studies on the impact of parental pension insurance on the marriage market, with most studies focusing on its impact on physical health, income level, life satisfaction, labor supply time, and female fertility. For example, Some economists reckon that the public pension model has the effect of lowering the fertility rate, which indirectly leads to a decline in the population and a decline in the marriage rate of the next generation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Janzen and Carter [44] found that an innovative microinsurance program had a smoothing effect on the consumption of rural households in Kenya. Zou et al [45] and He et al [46] found that participation in old-age insurance and health insurance played a significant positive role in household consumption. Bai and Wu [47] concluded from their study that the new cooperative health insurance scheme in China increased rural households' non-medical consumption.…”
Section: Influence Of Factors Preventing Motivation On Consumptionmentioning
confidence: 99%
“…The empirical results suggest that residents need to reduce their consumption of food and clothing, and thus reduce their total consumption in order to meet the need to pay for commercial insurance premiums. This study utilized commercial insurance premiums to derive a significant crowding out effect of precautionary money demand on household consumption, whereas the existing literature uses the presence or absence of insurance [45][46][47] and the number of insurance claims [44] to conclude that the precautionary feature of insurance increases household consumption. For government spending on social security, theoretically, it has a crowding-out effect on the consumption of targeted subsidies; on the other hand, it has an income effect on other consumption.…”
Section: Empirical Analysesmentioning
confidence: 99%